AI Revolution: How Artificial Intelligence Transforms the Face of Human Resources and Organizational Behavior (Management Studies and Business Journal (PRODUCTIVITY), 2024)
The artificial intelligence (AI) revolution has brought significant changes in various sectors, including in organizational structures and work patterns. Artificial intelligence, with its advanced analytical capabilities and process automation, has changed the way organizations operate and make decisions. This research aims to explore the impact of AI on organizational structures and work patterns in modern companies. The systematic literature review method with the PRISMA approach was used to collect and analyze relevant articles. The research results show that AI improves operational efficiency, cost savings, and productivity, but also brings challenges in terms of procedural fairness and employee burnout. The implications of this research include adjusting organizational structure and management, increasing decision-making efficiency, as well as changing organizational culture to reduce resistance to AI.